Factors Affecting The Success Of Pena Suasi (Family Assistance And Standby Husband) To The Success Of Labor Women In Kalangsari Village, Rengasdengklok District, Karawang Regency Year 2022 - Octora, Reni; Rismayanti, Tetin (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Based on an initial survey conducted by researchers in November 2023 at village midwives in Kalangsari Village, it was found that there were 38 primigravida mothers giving birth. Among the 38 primigravida patients, an observation was made that 25 primigravida mothers were not accompanied by their husbands when they were about to give birth. Thirteen primigravida mothers were accompanied by their husbands when they were about to give birth. The results of interviews with 13 primigravida mothers showed that the psychological condition of mothers who were accompanied by their husbands felt more confident and their level of anxiety was not too high compared to mothers who gave birth without their husbands' assistance. Objective: To know the factors that influence the success of PENA SUASI Karawang in 2022. Methodology: the research design is cross sectional. The sample used in this study was the total population, namely 30 mothers giving birth. The analysis used was the chi square test. Results: age, education, occupation and attitude, the only significant results being work, obtained a p-value of 0.005 (ơ <0.05) so it can be concluded that there is a significant influence between work and the success of PENASUASI in giving birth mothers. It is hoped that the family or the husband can understand more about the importance of Family Support and Standby Husband (PENASUASI) during the mother's pregnancy and childbirth.